Perfil epidemiológico da síndrome de eagle em radiografias do PROCEDE-UFU - Souza, Anny Isabelly dos Santos (2022)
The purpose of this work was to identify the prevalence of the Eagle syndrome in adult patients from Dentistry School, Federal University of Uberlândia, concerning age, sex, and side. It has been observed 463 panoramic radiographs, in which Eagle syndrome could be diagnosed when the length of styloid process exceeded 30 mm. The data were submitted to percentage calculation, and the chi-square test with significance level of 5% (p<0.05) has been applied to determine a possible association into sex and side. The results showed a prevalence of 83 cases of Eagle syndrome (17.9%), 51 men (61.4%) and 32 women (38.6%), 44 bilateral (53%), 29 on the right side (35%) and 10 on the left (12%). The most of these cases has been observed over the second and sixth decades of life. The higher prevalence in men and in the right side were statistically significant. We concluded that the Eagle syndrome is not a rare condition, and it is more prevalent in men from the age of 20, however, the sex factor seems be depending to a determined population studied. The bilateral occurrence is prevalent followed by right side. This epidemiological profile is an important tool for health professional and help to determine a clinical approach to the patient.